Konsep Diri : Definisi dan Faktor - Ramadona Dwi Marsela; Mamat Supriatna (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2019)
The purpose of this study is to understand the self control that exists in adolescentsregarding resolution and factors. There are two factors that influence self control, namely internal factors and external factors. Internal factors with age and external factors depend on the environment. The use of this paper is to develop a theory of self control and become a reference for future researchers.